The research progress and future directions in the pathophysiological mechanisms of type 2 diabetes mellitus from the perspective of precision medicine - Tian, Xinyi; Wang, Liuqing; Zhong, Liuting; Zhang, Kaiqi; Ge, Xiaolei; Luo, Zhengrong; Zhai, Xu; Liu, Shaoyan (Frontiers in Medicine, 2025)
Type 2 diabetes mellitus (T2DM) is a complex metabolic disorder characterized by pathophysiological mechanisms such as insulin resistance and β-cell dysfunction. Recent advancements in T2DM research have unveiled intricate multi-level regulatory networks and contributing factors underlying this disease. The emergence of precision medicine has introduced new perspectives and methodologies for understanding T2DM pathophysiology. A recent study found that personalized treatment based on genetic, metabolic, and microbiome data can improve the management of T2DM by more than 30%. This perspective aims to summarize the progress in T2DM pathophysiological research from the past 5 years and to outline potential directions for future studies within the framework of precision medicine. T2DM develops through the interplay of factors such as gut microbiota, genetic and epigenetic modifications, metabolic processes, mitophagy, NK cell activity, and environmental influences. Future research should focus on understanding insulin resistance, β-cell dysfunction, interactions between gut microbiota and their metabolites, and the regulatory roles of miRNA and genes. By leveraging artificial intelligence and integrating data from genomics, epigenomics, metabolomics, and microbiomics, researchers can gain deeper insights into the pathophysiological mechanisms and heterogeneity of T2DM. Additionally, exploring the combined effects and interactions of these factors may pave the way for more effective prevention strategies and personalized treatments for T2DM.